Toxic elements in benthic lacustrine sediments of Utah’s Great Salt Lake following a historic low in elevation - Jung, Julie; Frantz, Carie M.; Fernandez, Diego P.; Werner, Michael S. (Frontiers in Soil Science, 2024)
Terminal lakes (without outflow) retain elements and compounds that reach them through fluvial, point source or atmospheric deposition. If the lake sediment is exposed, some of these chemicals could become toxic dust particulates. The Great Salt Lake (GSL) in Utah is a terminal lake that experienced record-low lake elevation in 2021-22, exposing vast areas of playa. Here, we used inductively coupled plasma mass spectrometry to analyze the environmental chemistry of GSL shallow sediment during historic lows in spring, summer, and fall of 2021. Contaminants at the subsurface interface are most able to influence diffusion into the water column and uptake by benthic biota. We focused our analysis on copper, thallium, arsenic, mercury, lead, and zinc, which have been historically deposited in this region and are toxic when at high concentrations. We compared records of regional mining activity to understand the current contamination and assess relevant spatial and temporal gradients. We also used two different extraction methods (EPA 3050b and NH4AcO at pH=7) that can distinguish “environmentally available” vs. tightly associated and less available fractions. We observed consistent concentration of copper across sites indicating a larger relative impact of atmospheric deposition, with some evidence indicating further impacts of point sources. Arsenic, on the other hand, is maintained at high levels in submerged sediments and is likely geologically- and fluvially- derived. Thallium and mercury fluctuate seasonally and correlate with lake elevation. Lead and zinc levels are relatively low in GSL sites compared with freshwater input sites, indicating the deep brine layer may sequester these heavy metals, preventing their release into the water column. Overall, the concentrations of most metals in GSL sediments have declined from historic highs. However, each contaminant has distinct sources, seasonality, mobility and transmission. Complete recovery (if possible) may require many more decades and individual remediation strategies.